Hubungan Mutu Pelayanan Kesehatan Dengan Kepuasan Pasien Peserta BPJS Rawat Jalan Di Puskesmas - Emi Eliya Astutik (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2020)
Patient satisfaction is an indicator of the health service success in a clinic or hospital. There are five patient satisfaction index such as; Product Quality, Service Quality, Emotional Factor, Price And Cost Of Aquaring. In this study, the researcher concerns to examine the Service Quality of patient satisfaction index. There are five indicators of Service Quality such as physical evidence, reliability, assurance, response, and emphaty. The purpose of this study is identifying the relation between the Service Quality and patient satisfaction as BPJS outpatient member in Bangsalsari, Jember clinic. Methods this study conducts analytical survey by Cross Sectional approach. Moreover, the researcher uses Accidental Sampling technique in finding the sample. There are 62 outpatient respondents in Bangsalsari clinic. The result of data analysis is P Value 0,000 or p value < 0,01 by using Uji Koefisien Korelasi Spearman’s Rank. 43,5% respondents said that the service quality is good and 56,5 % respondents said it is very good. The conclusions of this study there are significant relation between the Service Quality and patient satisfaction of BPJS outpatient member in Bangsalsari clinic. Good service could increase patient satisfaction, especially in Bangsalsari Clinic.